FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI TEBU (Sacharum officinarum L) DI KECAMATAN PANGKAH KABUPATEN TEGAL - Rahmat Abi Alfatah; Dewi Hastuti; Rossi Prabowo (MEDIAGRO, 2019)
Purpose of this research is to know the acceptance level, income and the factors that is affecting the level of sugarcane farmers income. Regional sampling method and respondent sampling are conducted by purposive sampling method which is set a lend area sampled is 1 – 3,5 acres. Number of samples are taken by 59 respondents of the sugarcane farmers who are scattered in several villages at the Pangkah sub District. The analysis method used is descriptive analysis, cost analysis, revenue, income and multiple linear regression. The result of the study indicate that the average cost is obtained by the total cost Rp. 54.953.884. The revenue is obtained Rp. 82.979.127, while the income earned Rp. 28.025.243 every harvest time. The result of multiple liniear regression is known that the determination coefficient (R2) is 0.848. Meanwhile the result of testing t test obtained by educational factors have significant 0.042 which mean have a real impact to income at 5% real level. The ages factors have significant 0.001 which mean have a real impact to income at 1% real level. The land area have significant 0.044 which mean have a real impact to income at 5% real level. The labours have significant 0.001 which mean have a real impact to income at 1% real level. The amount of production have significant 0.000 which mean have a real impact to income at 1% real level. Keywords: Income, Sugarcane, farmers, Regression, Pangkah